Think before you shop: Analysis of impulsive buying of generation Z through influencer marketing - Lamarca, Abigail V. Leyson, Kimberly Anne, Relucio, Demarie B. Salinas, Trisha Anne P. 4 0 16; 5
Social media platforms are utilized by businesses in the Philippines to reach and engage with their potential customers. With Filipinos, particularly Gen-Z, being active on social media, influencer marketing has become a significant factor in shaping their purchasing behavior. This study aimed to analyze the effect of influencer marketing on impulsive buying of Generation Z in terms of influencers' photography, Influencers' videos, influencers' reviews, influencers' livestream, influencers' contests, influencers' unboxing, and influencers' takeover. Research respondents were obtained through convenience sampling of 208 Gen-Z who watch influencers on social media and perceive them as a reliable source of product recommendation. Data analysis was performed using correlation and chi-square tests. The findings revealed that Gen-Z's buying behaviors are significantly affected by influencer marketing through product videos and reviews. Furthermore, many of the respondents who watch influencer contents and trust their recommendations, have low levels of buyer's remorse. Research implies that Gen-Z consumers should practice cautious buying habits and mpower them to pause, reflect, and evaluate their purchases. With that, the archers came up with PAUSE mnemonic device which aims to reduce the impulsive buying behavior of Gen Zs. Keywords: influencer marketing, generation z, impulsive buying
Business Research: (BSBA major in Marketing Management) - Pamantasan ng Lungsod ng Maynila, 2024
Keywords: 2 -- 0; 6; 20; 20; 2